RANCANG BANGUN KEAMANAN WEB SERVICE DENGAN METODE WS-SECURITY DESIGN AND IMPLEMENTATION WEB SERVICE SECURITY WITH WS-SECURITY METHODS - , ari muzakir ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Web service uses XML technology to exchange data in. Generally, the use of the web service exchanges data or important information that needs to be guarded security. Form of security is applied to web services is to use public-key cryptography techniques. The attack can be a reconnaissance, destruction or theft of data. One way the best solution is to create data that can not read anyone else, even if someone else managed to retrieve the data, he will not be able to read it, security can be done using one of the encryption cryptographic techniques. The implementation was done by using the security library will provide facilities in developing a web security service for the library support XMLSEC as library supporters and library class_wss that have been built able to overcome the problem of security on the transport path, especially for authentication, authorization, and confidentiality request SOAP message. Model WS-Security using XML Signature, XML Encryption, and Security Token which utilizes the cryptographic algorithm RSA with 1024 bit key length to provide protection against transmission of data between client and server web service. Tests performed on the web service by implementing a security model class_wss library web service that is built to give good results, the SOAP request message is encrypted and decrypted with a good and able to sign and check their authenticity too.